Analysis of the Effectiveness of Waqf Management Benefits of Insurance and Investment Benefits in Takafulink Salam Waqf (Case Study at PT. Takaful Keluarga Medan Branch) - Putri Amanda, Dea; Atika, Atika (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2023)
The purpose of this study was to analyze the effectiveness of waqf management for investment benefits and insurance benefits for Takafulink Salam Waqf (a case study at PT. Takaful Keluarga Medan Branch). The method used in this research is descriptive qualitative research with the aim of making systematic and logical descriptions as well as research that aims to describe as accurately as possible something that becomes an object, symptom, or certain group so that later it will gain an understanding and understanding. The research results obtained are for the management of waqf insurance benefits and investment benefits of Takafulink Salam Waqf at PT. Takaful Keluarga Medan Branch. PT. Takaful Keluarga Medan Branch has been carried out effectively because all waqf management for insurance benefits and investment benefits is in accordance with the provisions of the MUI Fatwa and has also carried out the distribution of waqf management to parties who should receive it, which means the purpose and amount of the waqf distribution have also been implemented. in accordance with the management of waqf insurance benefits and investment benefits, themselves have been achieved where indeed their use is in accordance with the waqif pledge. And also where later when filling out the waqf form itself it is also filled in where the waqif wants the waqf to be registered at Indonesian Waqf Board (BWI), the objective of the effectiveness of waqf management is carried out by PT. Takaful Keluarga Medan Branch is not only compatible with the MUI Fatwa but also in accordance with the waqif pledge. Because of the management itself, PT. Takaful Keluarga Medan Branch cooperates with the Al Azhar Islamic Boarding School Foundation to manage the waqf funds that have been collected for further distribution throughout Indonesia and also regulates the participant’s waqf pledge deed. Thus, the implementation and achievement of the goals of the waqf itself are running effectively.